Pemberian Serbuk Daun Serai dan Daun Mengkudu terhadap Mortalitas Sitophilus oryzae L. pada Beras Siam Mutiara - Iqbal, Muhammad; Rizali, Akhmad; Apriani, Rila Rahma (Universitas Lambung Mangkurat, 2023)
Rice is one of the staple foods of the Indonesian people. Siam Mutiara Rice is local superior varieties of South Kalimantan which are in great demand by the people of Banjar. The supply of rice to meet the needs cannot be separated from the stock of rice in the storage warehouse. Long storage of rice often causes problems, one of which is the presence of Sitophilus oryzae L. The presence of these pests must be controlled so as not to damage both in terms of quality and quantity. the control that can be done is using botanical pesticides with the aim that these pests can be controlled but have no impact on humans who consume them. his study aims to determine the effect of effective administration of lemongrass and noni leaf powder on mortality, speed and weight loss in rice Siam Mutiara. This research was conducted in March 2021 – April 2021 at the Integrated Laboratory of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University. This study used a completely randomized design (CRD) 1 factor with treatment D0 (control/without application), D1 (15 g lemongrass leaf powder), D2 (15 g noni leaf powder), D3 (7.5 g lemongrass leaf powder; 7.5 g of noni leaf powder), D4 (10 g of lemongrass leaf powder; 5 g of noni leaf powder) and D5 (5 g of lemongrass leaf powder; 10 g of noni leaf powder). The treatment was repeated 4 times to obtain 24 experimental units. The results showed that the application of lemongrass and noni leaf powder was able to control and suppress the weight loss of Siam Mutiara rice. The effective treatment in controlling rice lice was D2 with a mortality percentage of 46.3%, a mortality rate of 0.4 head/day and was able to suppress rice weight loss by 0.2 g.